2012
DOI: 10.1021/es301376n
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage vs Single-Stage Thermophilic Anaerobic Digestion: Comparison of Energy Production and Biodegradation Efficiencies

Abstract: Two-stage anaerobic digestion (AD) for integrated biohydrogen and biomethane production from organic materials has been reported to promise higher process efficiency and energy recoveries as compared to traditional one-stage AD. This work presents a comparison between two-stage (reactors R1 and R2) and one-stage (reactor R3) AD systems, fed with identical organic substrates and loading rates, focusing the attention on chemical and microbiological aspects. Contrary to previous experiences, no significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(50 citation statements)
references
References 36 publications
4
41
1
4
Order By: Relevance
“…In the literature, two-stage digestion is usually reported to have a methanogenesis efficiency of 7%-23% (Shen et al, 2013;Liu et al, 2006;Lim et al, 2013) higher than one-stage digestion, while some studies found that the methane production in two-stage systems might be comparable or even inferior to single stage systems due to lower bacteria diversity and negative effects on the syntrophic association between acidogenens/acetogens and methanogens (Schievano et al, 2012;Merlino et al, 2013). Compared to two-stage digestion, storage treatment together with methane fermentation can already increase methane production by 40% in 21 and by 100% in 60 days as demonstrated in this study, and has great advantages in terms of economy and manipulation.…”
Section: Comparison With Two-stage Anaerobic Digestion Technologymentioning
confidence: 99%
“…In the literature, two-stage digestion is usually reported to have a methanogenesis efficiency of 7%-23% (Shen et al, 2013;Liu et al, 2006;Lim et al, 2013) higher than one-stage digestion, while some studies found that the methane production in two-stage systems might be comparable or even inferior to single stage systems due to lower bacteria diversity and negative effects on the syntrophic association between acidogenens/acetogens and methanogens (Schievano et al, 2012;Merlino et al, 2013). Compared to two-stage digestion, storage treatment together with methane fermentation can already increase methane production by 40% in 21 and by 100% in 60 days as demonstrated in this study, and has great advantages in terms of economy and manipulation.…”
Section: Comparison With Two-stage Anaerobic Digestion Technologymentioning
confidence: 99%
“…[15] The specific methane yield in two-phase systems during the fermentation of glucose solutions, organic waste and household waste was up to 24% higher than in single-phase systems. [16][17][18][19] A further experiment of Lehtomäki and Björnsson [20] showed a 5% higher methane yield in a two-stage pilot-scale reactor compared with a laboratory batch system digesting grass. Another major advantage of the two-phase process is the fractionation of the gases during anaerobic digestion.…”
Section: Introductionmentioning
confidence: 96%
“…Hence, it is significant to develop the high-rate methane production system using POME. Normally, the optimum pH for hydrogen production is 5.5e6.0 and a large amount of sodium hydroxide, which is used for pH adjustment can increase the production cost as well [14]. The POME generated at a high temperature of around 80e90 C from its source.…”
Section: Introductionmentioning
confidence: 99%